2013
DOI: 10.3168/jds.2013-6824
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quantitative trait loci underlying milk traits in Spanish dairy sheep using linkage plus combined linkage disequilibrium and linkage analysis approaches

Abstract: In this study, 2 procedures were used to analyze a data set from a whole-genome scan, one based on linkage analysis information and the other combing linkage disequilibrium and linkage analysis (LDLA), to determine the quantitative trait loci (QTL) influencing milk production traits in sheep. A total of 1,696 animals from 16 half-sib families were genotyped using the OvineSNP50 BeadChip (Illumina Inc., San Diego, CA) and analysis was performed using a daughter design. Moreover, the same data set has been previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
(43 reference statements)
3
18
0
1
Order By: Relevance
“…Under the conservative assumption that underlying causal genetic variants are the same (or are at least located on the same genes), the present study could help refine the confidence intervals of these bovine QTLs. We also found an orthologous ovine QTL for CHI 5 45 , for CHI 19 but with a large interval (up to 30 Mb) 46,47 and for CHI 21 48 .…”
Section: Discussionsupporting
confidence: 56%
“…Under the conservative assumption that underlying causal genetic variants are the same (or are at least located on the same genes), the present study could help refine the confidence intervals of these bovine QTLs. We also found an orthologous ovine QTL for CHI 5 45 , for CHI 19 but with a large interval (up to 30 Mb) 46,47 and for CHI 21 48 .…”
Section: Discussionsupporting
confidence: 56%
“…An SNP was considered to be from a particular gene if it mapped within it. The QTLs were located in the database Jbrowse [35], using online page (https://www.animalgenome.org/) which contains QTLs previously reported in sheep [36][37][38][39].…”
Section: Candidate Gene and Qtls Associatedmentioning
confidence: 99%
“…as follows: GO:0001701: in uterus embryonic development (ANKRD11); GO:0008585: female gonad development (ARID5B); GO:0070373: negative regulation of ERK1 and ERK2 cascade (DLG1); GO:0032870: cellular response to hormone stimulus (ROBO2); GO:0061364: apoptotic process involved in luteolysis (ROBO2); GO:0032275: luteinizing hormone secretion (CGA); GO:0032870: cellular response to hormone stimulus (CGA); GO:0046621: negative regulation of organ growth (CGA); GO:0046884: follicle-stimulating hormone secretion (CGA). The SNPs were used to identify QTLs previously localized in other studies performed in other sheep populations [36][37][38][39], and all QTLs are shown in Table S2. The analysis of the metabolic pathways in which the significant genes participate, showed that 12 genes are associated with some metabolic pathway ( Table 1).…”
Section: Gene Ontology and Kegg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to find genes associated with ovine milk traits, researchers have conducted a selection signature analysis between five non-milk sheep breeds and five milk sheep breeds, and they have identified some milk-related genes such as ABCG2 and SPP1 (Gutierrez-Gil et al, 2014). However, this previous study still had some limitations in experimental design.…”
Section: Introductionmentioning
confidence: 99%